1967
DOI: 10.1620/tjem.93.317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vagotomy or Splanchnicectomy on the Motility of the Canine Stomach with Transection-anastomosis

Abstract: Transection-anastomosis of the canine stomach generally caused frequent development of vigorous anti-peristalsis in the portion distal to the anastomosis. With the use of electromyography, effect of vagotomy or splanchnicectomy on this alteration of the gastric motility was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…To answer this question, two experimental studies were performed on the appearance of the pacemaker in dogs. One study, in which the stomach after the transection-anastomosis with truncal vagotomy was evaluated by electromyogram, showed that a new pacemaker zone appeared at the most oral region of transection and its discharge rate was slower than normal (3). In the other study, Hoshikawa et al showed that, after proximal gastrectomy, the amplitude of action potentials was generally low, resting phases appeared occasionally, and the control activity-like waves appeared preprandially, but the interval and duration of these waves were irregular and no synchronized electrical activity was transmitted between the residual stomach and the duodenum (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer this question, two experimental studies were performed on the appearance of the pacemaker in dogs. One study, in which the stomach after the transection-anastomosis with truncal vagotomy was evaluated by electromyogram, showed that a new pacemaker zone appeared at the most oral region of transection and its discharge rate was slower than normal (3). In the other study, Hoshikawa et al showed that, after proximal gastrectomy, the amplitude of action potentials was generally low, resting phases appeared occasionally, and the control activity-like waves appeared preprandially, but the interval and duration of these waves were irregular and no synchronized electrical activity was transmitted between the residual stomach and the duodenum (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiological function of the residual stomach after proximal gastrectomy has not been clearly evaluated in humans. As a possible cause of the delayed gastric emptying for residual stomach, some authors mentioned the influences of truncal vagotomy or transection of the stomach in the era when gastrectomy was done for peptic ulcer (3,4). Moreover, there have been no reports on whether spontaneous contractions of the residual stomach occur, whether there is a relationship between gastric removal volume and spontaneous contractions, or whether there is a relationship between residual gastric volume and electrical activity in patients after proximal gastrectomy.…”
mentioning
confidence: 99%
“…This may be the reason for requiring an additional drainage procedure to avoid the delayed emptying in cases with conventional segmental gastric resection. Shiratori et al [16] also verified electromyographically that the development of antiperistaltic discharges after transection-anastomosis was not related primarily to the severance of vagal innervation of the stomach, but was closely related to the excitement of the antral wall per se caused by the transection at the distal portion of the stomach. Successively, Shiratori et al [17] carried out a manometric and electrornyographical study to elucidate the relationship between the level of transection and the contraction pressure of the pylorus in the canine stomach.…”
Section: Commentmentioning
confidence: 91%
“…1A). 10 Maki's colleagues summarized the long-term results of PPG in 1992. 11 A report on the outcomes of 134 patients followed up over 25 years revealed peptic ulcer recurrence in 5.4% and dumping syndrome in only 4.4% and 0% as determined by questionnaire and interview, respectively.…”
Section: For Gastric Ulcersmentioning
confidence: 99%